Innovating Green: Competition Meets Regulation - Dai, Rui; Duan, Rui; Ng, Lilian (Management Science, 2026)
This study shows that competition drives corporate innovation under intense environmental regulatory pressure. Using the nonattainment status of U.S. counties as an exogenous variation in regulation, we find that competition spurs green innovation as firms respond to stricter policies. Firms are particularly motivated to innovate in clean technology when operating in pollution-intensive industries, facing high relocation costs, and possessing a strong history of innovation. Regulation-driven green innovation allows firms to differentiate their products, enhance their environmental, social, and governance (ESG) reputation, and attract more corporate customers, leading to higher sales growth, increased market share, and improved profitability, although not necessarily higher valuation. Stricter regulations in competitive environments not only curb pollution but also serve as a catalyst for sustainable long-term innovation. These findings emphasize the vital role of environmental regulations in promoting sustainable practices and operational benefits, underscoring the importance of well-designed policies to drive long-term economic and environmental progress. This paper was accepted by Bo Becker, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2023.00600 .